Measuring the Performance of Local Government Entities and Analysis of their Managers' and Personnel's Information Needs in the Context of "New Public Management"; Pomiar dokonaní analiza potrzeb informacyjnych menedzėroẃ i pracownikoẃ jednostek samorzadu terytorialnego w konteksćie "New Public Management" - Ewelina Zarzycka; Marcin Michalak (Comparative Economic Research. Central and Eastern Europe, 2013)
Ways to make the public sector more effective and efficient have been vigorously discussed for more than thirty years by practitioners and researchers all over the world. Public sector reforms drawing on the paradigm of an entrepreneurial and market style of management are called New Public Management (NPM). However if the concept of managing public sector entities according to the best management practices in the private sector is to be implemented and used effectively, the necessary management-aid tools must be introduced. This particularly applies to the public sector's accounting system oriented to external reporting, to which needs to be added a management accounting subsystem with cost accounting and budgeting based on responsibility accounting and a measurement, evaluation, and performance reporting subsystem. The main research objectives of this article are the following: ~- to identify the management accounting methods and tools currently used by the managers of sampled local government entities (LGEs); ~- to identify the information needs of the LGEs' managers and personnel related to the implementation and application of a management accounting system, and to find out what accounting methods and tools they would like to have at their disposal to improve management processes; ~- to evaluate the usefulness, adequacy and effectiveness of performance measurement systems used in LGEs. This article fits into the scope of world research on the implementations of the NPM concept and uses New Institutional Economy to better understand the implementation of management accounting in the public sector. – – Rozrost sektora publicznego i postepujacy w nim kryzys wartosći przyczyniły sie do podjecia w wielu krajach głebokich reform tego sektora, bazujacych na paradygmacie menedzėrskiego i rynkowego stylu zarzadzania, ktoŕe zyskały miano New Public Management - NPM. Wdrozėnie i skuteczne wykorzystanie koncepcji zarzadzania jednostkami sektora publicznego, bazujacej na dobrych praktykach zarzadzania organizacjami biznesowymi, wymaga implementacji odpowiednich narzedzi rachunkowosći zarzadczej wpierajacych procesy zarzadcze. Głoẃne cele badawcze przyjete przez autoroẃ tego artykułu obejmuja: ~- identyfikacje metod i narzedzi rachunkowosći zarzadczej stosowanych aktualnie przez kierownikoẃ badanych jednostek samorzadu terytorialnego; ~- analize potrzeb informacyjnych kierownikoẃ i pracownikoẃ jednostek samorzadu terytorialnego w obliczu wdrazȧnia i stosowania systemu kontroli zarzadczej, ~- ocene przydatnosći, adekwatnosći i skutecznosći systemu pomiaru dokonanśtosowanego przez jednostki samorzadu terytorialnego w Polsce, a takzė stopnia spełnienia przez niego wymogoẃ prawnych, w konteksćie załozėnśystemu kontroli zarzadczej oraz koncepcji NPM. Badanie zostało przeprowadzone w formie wywiadu - ankiety audytoryjnej, skierowanej do 45 respondentoẃ reprezentujacych jednostki samorzadu terytorialnego. Uzyskane rezultaty potwierdzaja, izṡystem pomiaru dokonanśtosowany przez jednostki samorzadu terytorialnego w Polsce jest wynikiem silnego oddziaływania instytucjonalnego na system zarzadzania tymi jednostkami i nie jest przydatny dla kierownikoẃ i pracownikoẃ tego sektora, a takzė nie spełnia wymaganśtawianych przez załozėnia koncepcji NPM.
Keywords: 330